2004
DOI: 10.3171/jns.2004.101.1.0154
|View full text |Cite
|
Sign up to set email alerts
|

Intentional partial coil occlusion followed by delayed clip application to wide-necked middle cerebral artery aneurysms in patients presenting with severe vasospasm

Abstract: The treatment of ruptured cerebral aneurysms in patients presenting with vasospasm remains a particular challenge. The authors treated two patients harboring Hunt and Hess Grade 1 subarachnoid hemorrhages from middle cerebral artery (MCA) aneurysms associated with severe local angiographically demonstrated yet asymptomatic vasospasm on presentation. Because both aneurysms had wide necks and were located at the MCA bifurcation, they were believed to be anatomically suitable for microsurgical clip application. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…A thorough examination of the literature has revealed the successful treatment of these lesions by open surgical and combined open and endovascular approaches. [31][32][33][34] Undoubtedly, a significant role for open surgical intervention remains; however, the diminished operative time and minimally invasive nature of endovascular intervention have been shown to improve outcomes. This finding has been especially true in patients with higher-grade hemorrhages, multiple comorbidities, or advanced age.…”
Section: Selection Of Stent-assisted Coiling and Evaluation Of Alternmentioning
confidence: 99%
“…A thorough examination of the literature has revealed the successful treatment of these lesions by open surgical and combined open and endovascular approaches. [31][32][33][34] Undoubtedly, a significant role for open surgical intervention remains; however, the diminished operative time and minimally invasive nature of endovascular intervention have been shown to improve outcomes. This finding has been especially true in patients with higher-grade hemorrhages, multiple comorbidities, or advanced age.…”
Section: Selection Of Stent-assisted Coiling and Evaluation Of Alternmentioning
confidence: 99%
“…A good outcome was reported in this series that included partially coiled aneurysms, aneurysm recurrence, and/or re-rupture after coiling (41). In patients presenting with severe vasospasm, partial coiling followed by staged definitive clipping is a good algorithm to avoid microsurgical manipulation of vessels in the setting of vasospasm (42). Rabenstein et al reported a high incidence of vasospasm in SAH patients treated with clipping versus coiling (43).…”
Section: Surgical Treatment After Endovascular Therapymentioning
confidence: 99%
“…In particular, the endovascular procedure causes fewer ischemic complications during the vasospasm phase in patients with SAH. 1,7) In this case, coil embolization was appropriate to avoid re-bleeding in the acute period.…”
Section: Discussionmentioning
confidence: 91%